The American Heritage dictionary idioms - Ammr, Christine (United states of America houghton mifflin harcourt, 2003)
This book is the largest collection of idioms and popular phrasee available today. its main fare is idioms - groups of two or more words that taken together mean something different from the literal meaning of the individual words. each entry is defind and has an example sentence showing the idioms used in context. most entries offer an explanation of the idioms's literal meaning or origin and include information about its first appearance in english
American Corner
11
Keywords: Americanisms -- dictionaries; English language -- idioms -- dictionaries; English language -- terms and phrases